Creating and utilizing spaces to enhance intergenerational learning at schools and results - Soner Polat; Yıldız Okçu; Çağlar Çelik (Institute of Advanced Engineering and Science, 2019)
The purpose of the study was to explore the requirements of schools to increase intergenerational learning, collaboration and solidarity amongst the Baby Boomers, X and Y generations, based on the views of school principals. The research focused on how to create spaces for interaction among different generations and what consequences will arise when intergenerational spaces are created. This study was conducted with phenomenological research design. The study group consisted of 12 school principals who were identified with the maximum diversity sampling technique from Kocaeli Province, Dilovasi District. Criteria used in the selection of school principals were to work as managers in different schools and in different school types. The data were collected with a semi-structured interview form and the content analysis method was used. Interview questions were determined by researchers in the direction of research questions. Creation of intergenerational space is the main topic of this study whereas subtopics are scope and opportunities. On the other hand, findings collected indicate that principals mention intramural and out of school events about the creation of intergenerational space. These events are met under the titles of sports, art, entertainments and educational space. Finally, the results of creating spaces were examined in the study.